Acrylate-epoxy resin composite coating and preparation method thereof

By using core-shell structured corrosion-inhibiting nanocontainers made of acrylate-epoxy resin composite coatings and functionalized graphene quantum dots, combined with photo-thermal dual-responsive curing agents, the problem of corrosion prevention and damage detection for marine engineering equipment in extreme environments has been solved, achieving self-repair and high-efficiency protection.

CN121022192APending Publication Date: 2025-11-28深圳市深赛尔股份有限公司
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202511373015.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-24
Publication Date
2025-11-28

AI Technical Summary

Technical Problem

Existing anti-corrosion coatings for marine engineering equipment suffer from problems such as rapid penetration of corrosive media after coating damage in extreme environments, poor wear resistance, insufficient impact toughness, limited self-healing ability, and difficulty in damage detection. Furthermore, graphene has failed to fulfill its electrochemical shielding and damage visualization diagnostic functions.

Method used

An acrylic-epoxy resin composite coating is used, which uses a core-shell structured corrosion-inhibiting nano-container to accurately sense corrosion, functionalized graphene quantum dots to achieve damage fluorescence tracing, and a photo-thermal dual-responsive curing agent to form a self-healing and electrochemically protective coating that takes into account both long-term corrosion protection and dynamic adaptability.

Benefits of technology

It achieves the coating's self-healing capability, non-destructive rapid location and accurate diagnosis of damage, improves the full-cycle economy and protective effect of marine equipment, and reduces maintenance costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121022192A_ABST
    Figure CN121022192A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of coatings, in particular to an acrylate-epoxy resin composite coating and a preparation method thereof. According to the technical scheme, the coating is prepared from 25 to 35 parts of methyl methacrylate, 15 to 25 parts of butyl acrylate, 10 to 20 parts of epoxy resin E-5110, 8 to 15 parts of organic silicon modified acrylate prepolymer, 5 to 12 parts of fluorocarbon modified epoxy resin, 4 to 8 parts of core-shell structure corrosion inhibition nano container, 1 to 3 parts of functionalized graphene quantum dots and 4 to 10 parts of polyhedral oligomeric silsesquioxane maleimide modified amine curing agent. And 1-3 parts of a hindered amine light stabilizer. By integrating the core-shell structure corrosion inhibition nano container, the functionalized graphene quantum dots and the photo-thermal dual responsive curing agent component, the sensing, response and self-repairing of the coating on damage are realized, and long-acting corrosion resistance, weather resistance, bacteria resistance, mechanical property balance and intelligent maintenance are considered; and efficient and economical full-period protection is provided for equipment in an extreme environment.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of coating, in particular to an acrylate-epoxy resin composite coating and a preparation method thereof. BACKGROUND

[0002] The marine engineering equipment is exposed to the extreme environment of high salt, high humidity, strong ultraviolet and microbial corrosion for a long time. Although the traditional epoxy-acrylate anticorrosive coating has basic protection performance, it has three technical bottlenecks: firstly, after the coating is damaged, the corrosion medium penetrates along the defect quickly, causing substrate pitting and cathodic delamination, and the conventional physical barrier function fails and cannot be repaired automatically; secondly, the existing nano-enhanced fillers (such as graphene microsheet and silicon dioxide) have poor dispersion stability in the resin matrix, which easily causes interface peeling, resulting in a sharp decrease in wear resistance, and there is a lack of real-time monitoring mechanism for corrosion state; thirdly, the rigid solidification network leads to insufficient impact toughness, and the addition of flexible components easily sacrifices chemical resistance, making it difficult to balance long-term protection and dynamic service adaptability.

[0003] Current self-repairing coatings mostly rely on microcapsule technology, and the repair behavior is single and the repair efficiency significantly decreases with aging; some studies introduce corrosion inhibitors directly blended, but there is a problem of shortened protection life caused by non-controlled release. The dual system of photocuring / thermocuring can improve construction efficiency, but it does not solve the problem of dynamic reconstruction of the network, which makes it impossible to inhibit the expansion of microcracks. In addition, in the existing technology, graphene is mainly used as a physical barrier filler, and its composite functions of electrochemical shielding and damage visual diagnosis cannot be developed.

[0004] In view of the above, the present application provides an acrylate-epoxy resin composite coating and a preparation method thereof. SUMMARY

[0005] The purpose of the present application is to solve the problem of long-term performance and functional integration of marine anticorrosive coatings in the background art, and to provide an acrylate-epoxy resin composite coating and a preparation method thereof.

[0006] In a first aspect, the present application provides an acrylate-epoxy resin composite coating, which comprises the following raw materials by weight: Methyl methacrylate 25-35 parts, butyl acrylate 15-25 parts, epoxy resin E-5110-20 parts, silicone-modified acrylate prepolymer 8-15 parts, fluorocarbon-modified epoxy resin 5-12 parts, core-shell structure corrosion inhibition nano container 4-8 parts, functionalized graphene quantum dot 1-3 parts, cage-type silsesquioxane maleimide modified amine curing agent 4-10 parts, hindered amine light stabilizer 1-3 parts, modified nano zinc oxide 2-6 parts, titanate coupling agent 0.5-2 parts, light-thermal dual-responsive curing agent 2-5 parts, dibutyltin dilaurate 0.1-0.5 parts, propylene glycol methyl ether acetate 10-20 parts, butyl acetate 5-15 parts.

[0007] Optionally, the core-shell structure corrosion inhibitor nano-container is prepared by the following method: 8-12 parts of nano-silica with a particle size of 10-30 nm is dispersed in a mixture of ethanol / water (1:1), 3-5 parts of benzotriazole is added, and ultrasonic dispersion is performed for 25-35 minutes; a monomer mixture containing 8-12 parts of dimethylaminoethyl methacrylate and 1-2 parts of ethylene glycol dimethacrylate is added dropwise, nitrogen is introduced, and 0.2-0.4 parts of azobisisobutyronitrile is added, and reaction is performed at 60-70°C for 5-7 hours; after centrifugal washing and drying, a core-shell structure corrosion inhibitor nano-container with a corrosion inhibitor loading of 20-25 wt% is obtained.

[0008] Optionally, the functionalized graphene quantum dot is prepared as follows: The graphene quantum dot oxide is dispersed in ammonia water with pH=9, 6-8 parts of tridecafluorooctyltriethoxysilane and 3-5 parts of γ-glycidoxypropyltrimethoxysilane are added, and stirring reaction is performed at 70-80°C for 16-20 hours; after dialysis to remove small molecules, freeze-drying is performed to obtain the functionalized graphene quantum dot grafted with double functional groups.

[0009] Optionally, the cage silsesquioxane maleimide modified amine curing agent is prepared by the following method: 40-50 parts of isobutyltrichlorosilane is dissolved in 80-100 parts of toluene, and under ice water bath cooling, 25-35 parts of deionized water and 15-20 parts of triethylamine are slowly added dropwise; after the dropwise addition is completed, the temperature is increased to 80-110°C for reflux reaction for 8-12 hours; after the reaction is completed, the generated salt is removed by filtration, and the solvent is removed by distillation under reduced pressure to obtain 30-40 parts of isobutyl cage silsesquioxane; The above isobutyl cage silsesquioxane 30-40 parts is dissolved in toluene 60-80 parts, 3-aminopropyltriethoxysilane 8-12 parts and stannic octoate 0.5-1 parts are added, and the temperature is increased to 100-120°C for reaction under nitrogen protection for 10-16 hours; after the reaction is completed, the unreacted monomer and solvent are removed by distillation under reduced pressure to obtain 23-27 parts of aminopropyl isobutyl cage silsesquioxane; The aminopropyl isobutyl cage silsesquioxane 23-27 parts is dissolved in toluene, N-(2-aminoethyl) maleimide 10-14 parts is added, and reaction is performed at 65-75°C for 4-6 hours; the solvent is removed under reduced pressure to obtain the cage silsesquioxane maleimide modified amine curing agent.

[0010] Optionally, the light-heat dual-responsive curing agent is furanmethylamine-2-hydroxy-2-methylpropiophenone adduct, and the structural formula is: (CH3)2C(OH)C(=NCH2C4H3O)C(O)CH3.

[0011] Optionally, the modified nano-zinc oxide is prepared by the following method: The nano-zinc oxide powder with a particle size of 20-50 nm is dispersed in anhydrous ethanol at 8-12 parts, and ultrasonic treatment is performed for 25-35 minutes to form a suspension; After heating to 60±2℃, stearic acid-ethanol solution is added dropwise, the amount of stearic acid is 15-25% of the mass of nano-zinc oxide, and stirring reaction is performed under nitrogen protection for 3-5 hours; After the reaction is completed, centrifugal separation is performed, washing is performed 2-4 times with anhydrous ethanol, and vacuum drying is performed at 75-85℃ for 10-14 hours to obtain nano-zinc oxide with surface organic modification.

[0012] Optionally, the photo-thermal dual-responsive curing agent is prepared by the following method: By weight parts, 2-furfuryl aldehyde 13-17 parts and anhydrous ethanol 28-32 parts are mixed, ice bath cooling to 0-5℃, slowly drop 8-12 parts of concentrated ammonia water, keep the temperature <10℃, after dropping, the temperature is raised to 23-27℃, and the reaction is carried out for 1-3 hours, 4-6 parts of sodium borohydride is added, and the reduction reaction is carried out at 35-45℃ for 2-4 hours, the solvent is removed by reduced pressure distillation, and the crude furfuryl amine is obtained; By weight parts, 8-12 parts of furfuryl amine obtained in step one, 10-14 parts of 2-hydroxy-2-methylbenzophenone, 45-55 parts of toluene, 0.3-0.7 parts of p-toluenesulfonic acid are added, heated to 110±2℃, refluxed for 5-7 hours, the reaction liquid is cooled, washed with water until neutral, dried with anhydrous magnesium sulfate, and toluene is removed by reduced pressure distillation to obtain a yellow viscous liquid, which is the photo-thermal dual-responsive curing agent.

[0013] In a second aspect, the application provides a preparation method of the acrylate-epoxy resin composite coating as described in the first aspect, comprising the following steps: S1, methyl methacrylate, butyl acrylate, propylene glycol methyl ether acetate and butyl acetate are added to a reaction kettle, heated to 80-90℃, 8-12 parts of butyl acetate solution containing 2-4 parts of azobisisobutyronitrile is added dropwise, and the dropping is completed within 2-3 hours, and the reaction is kept for 3-4 hours to obtain an acrylate prepolymer; S2, epoxy resin E-51, fluorocarbon modified epoxy resin, and silicone modified acrylate prepolymer are added to the acrylate prepolymer, and stirring is performed at 60-70℃ for 2-3 hours to obtain a preliminary treatment; S3, adding the core-shell structure corrosion inhibition nano container, functionalized graphene quantum dots and modified nano zinc oxide into the primary processing material, ultrasonic dispersion for 1-2 hours under a power of 550-650 W and a frequency of 20-30 kHz to obtain an intermediate processing material, the intermediate processing material containing solid fillers including the core-shell structure corrosion inhibition nano container, the functionalized graphene quantum dots and the modified nano zinc oxide, detecting a dispersion coefficient of the solid fillers, and adjusting the dispersion coefficient of the solid fillers until the dispersion coefficient is ≤15%, the dispersion coefficient being calculated according to the following formula: In the formula, represents the core-shell structure corrosion inhibition nano container, represents the functionalized graphene quantum dots, represents the modified nano zinc oxide, is a functional weight coefficient, wherein = 0.4, = 0.35, = 0.25, is a particle size influence coefficient, wherein = 1.2, = 1.3, = 1.0, is a measured average particle size of a single filler, is a measured particle size distribution standard deviation of the single filler; After the dispersion coefficient meets the standard, a titanate coupling agent is added to the intermediate processing material and reacted at 50-60℃ for 1-2 hours. S4, cooling to 30-40℃, adding a hindered amine light stabilizer, dibutyltin dilaurate, a light-heat dual-responsive curing agent and a cage-type silsesquioxane maleimide modified amine curing agent, stirring for 30-50 minutes, and high-speed dispersing for 10-30 minutes. S5, filtering to obtain a coating.

[0014] Optionally, in the S3, the ultrasonic power is 550-650 W and the frequency is 20-30 kHz.

[0015] Optionally, in the S4, first stirring at 800 r / min for 30-50 minutes, and then high-speed dispersing at 2500 r / min for 10-30 minutes.

[0016] Compared with the prior art, the present application has at least one of the following beneficial technical effects: The core-shell corrosion inhibition nano container precisely senses the change of the corrosion microenvironment and releases the corrosion inhibitor in the damage area, breaking through the limitation that the traditional coating fails when damaged, and realizing the blocking of the corrosion process.

[0017] The optical response characteristics of the coating are endowed by functionalized graphene quantum dots, the fluorescence of the damage points is traced by ultraviolet excitation, the micron-level defect is positioned rapidly and nondestructively, and the passive maintenance mode relying on manual detection is completely changed. The uniform doping of the functionalized graphene quantum dots is the basis, and the interface state change, medium penetration and light scattering change caused by damage are the core of the fluorescence specificity enhancement. This characteristic can not only uniformly disperse to ensure the overall performance of the coating, but also realize accurate positioning through fluorescence signal mutation at the defect, and completely solve the problem that the micron-level damage is difficult to be found by traditional manual detection.

[0018] The present application integrates damage diagnosis, corrosion inhibitor targeted delivery and electrochemical protection into a single coating, realizes effective protection, combines the rigid cage-type silsesquioxane skeleton with the structure with deformable characteristics, takes into account high hardness and impact toughness, overcomes the performance imbalance defect of traditional coatings, reduces maintenance cost through fluorescence diagnosis, reduces re-coating frequency through self-repairing ability, and greatly improves the whole-cycle economy of marine equipment.

[0019] The coating of the present application integrates the corrosion-inhibiting nano-container with core-shell structure, functionalized graphene quantum dots and light-heat dual-responsive curing agent components, so that the coating formed by the coating has long-term corrosion resistance, weather resistance, antibacterial property, balanced mechanical property and maintenance, and provides efficient and economical whole-cycle protection for equipment in extreme environments. BRIEF DESCRIPTION OF DRAWINGS

[0020] Figure 1 A flowchart of a preparation method of an acrylate-epoxy resin composite coating. DETAILED DESCRIPTION

[0021] The embodiments of the present application are described below through specific specific examples, and those skilled in the art can easily understand other advantages and effects of the present application from the disclosure in the specification. The present application can also be implemented or applied by other different specific embodiments, and the details in the specification can be modified or changed based on different views and applications without departing from the spirit of the present application. It should be noted that the following examples and features in the examples can be combined with each other without conflict.

[0022] Example 1 The acrylate-epoxy resin composite coating comprises the following raw materials by weight: Methyl methacrylate 25 parts, butyl acrylate 15 parts, epoxy resin E-5110 parts, silicone-modified acrylate prepolymer 8 parts, fluorocarbon-modified epoxy resin 5 parts, core-shell structure corrosion inhibitor nano container 4 parts, functionalized graphene quantum dots 1 part, cage-type silsesquioxane maleimide modified amine curing agent 4 parts, hindered amine light stabilizer 1 part, modified nano zinc oxide 2 parts, titanate coupling agent 0.5 parts, light-heat dual-responsive curing agent 2 parts, dibutyltin dilaurate 0.1 parts, propylene glycol methyl ether acetate 10 parts, butyl acetate 5 parts.

[0023] The core-shell structure corrosion inhibitor nano container is prepared by the following method: dispersing 8 parts of nano silicon dioxide with a particle size of 10-30 nm in a mixture of ethanol / water in a volume ratio of 1:1, adding 3 parts of benzotriazole, and ultrasonic dispersion for 25 minutes; drop 8 parts of monomer mixture containing dimethylaminoethyl methacrylate and 1 part of ethylene glycol dimethyl acrylate, add azobisisobutyronitrile 0.2 parts after nitrogen purging, and react at 60℃ for 5 hours; centrifugal washing and drying to obtain a core-shell structure corrosion inhibitor nano container with a corrosion inhibitor loading of 20wt%.

[0024] In addition, the functionalized graphene quantum dots are prepared as follows: dispersing graphene oxide quantum dots in ammonia water with pH=9, adding tridecafluorooctyltriethoxysilane 6 parts and γ-glycidyl ether oxypropyltrimethoxysilane 3 parts, and stirring at 70℃ for 16 hours; dialysis to remove small molecules and freeze-drying to obtain functionalized graphene quantum dots grafted with double functional groups.

[0025] The cage-type silsesquioxane maleimide modified amine curing agent is prepared by the following method: dissolving isobutyltrichlorosilane 40 parts in toluene 80 parts, slowly adding deionized water 25 parts under ice water bath cooling, adding triethylamine 15 parts at the same time, and then increasing the temperature to 80℃ for reflux reaction for 8 hours; after the reaction is completed, the generated salt is removed by filtration, and the solvent is removed by reduced pressure distillation to obtain isobutyl cage-type silsesquioxane 30 parts; The above isobutyl cage-type silsesquioxane 30 parts is dissolved in toluene 60 parts, 3-aminopropyltriethoxysilane 8 parts and tin octoate 0.5 parts are added, and the temperature is increased to 100℃ under nitrogen protection for 10 hours. After the reaction is completed, the unreacted monomers and solvents are removed by reduced pressure distillation to obtain aminopropyl isobutyl cage-type silsesquioxane 23 parts. The aminopropyl isobutyl cage-type silsesquioxane 23 parts is dissolved in toluene, N-(2-aminoethyl) maleimide 10 parts is added, and the temperature is increased to 65℃ for 4 hours. The solvent is removed by reduced pressure to obtain a cage-type silsesquioxane maleimide modified amine curing agent.

[0026] The photo-thermal dual-responsive curing agent is furanylamine-2-hydroxy-2-methylphenylacetone adduct, and its structural formula is: (CH3)2C(OH)C(=NCH2C4H3O)C(O)CH3.

[0027] Modified nano zinc oxide was prepared by the following method: 8 parts of nano zinc oxide powder with a particle size of 20-50 nm were dispersed in anhydrous ethanol and ultrasonically treated for 25 minutes to form a suspension; after heating to 60±2℃, a stearic acid-ethanol solution was added dropwise, with the amount of stearic acid being 15% of the mass of nano zinc oxide, and the reaction was stirred for 3 hours under nitrogen protection; after the reaction was completed, the mixture was centrifuged, washed twice with anhydrous ethanol, and vacuum dried at 75℃ for 10 hours to obtain surface organically modified nano zinc oxide.

[0028] It should be noted that the photo-thermal dual-responsive curing agent is prepared by the following method: Step 1: Mix 13 parts by weight of 2-furan carbaldehyde with 28 parts by weight of anhydrous ethanol and cool to 0°C in an ice bath; slowly add 8 parts by weight of concentrated ammonia water while maintaining the temperature <10°C; after the addition is complete, raise the temperature to 23°C and react for 1 hour; add 4 parts by weight of sodium borohydride and reduce the reaction at 35°C for 2 hours; remove the solvent by vacuum distillation to obtain crude furanylamine. Step 2: By weight, add 8 parts of furanylmethylamine and 10 parts of 2-hydroxy-2-methylphenylacetone obtained in Step 1 to 45 parts of toluene, and add 0.3 parts of p-toluenesulfonic acid; heat to 110±2℃ and reflux for 5 hours; after cooling the reaction solution, wash with water until neutral, dry with anhydrous magnesium sulfate, and remove toluene by vacuum distillation to obtain a yellow viscous liquid, which is the photo-thermal dual-responsive curing agent.

[0029] like Figure 1 The preparation method of acrylate-epoxy resin composite coating includes the following steps: S1. Add methyl methacrylate, butyl acrylate, propylene glycol methyl ether acetate and butyl acetate to a reaction vessel, heat to 80°C, and dropwise add 8 parts of butyl acetate solution containing 2 parts of azobisisobutyronitrile. The dropwise addition is completed within 2 hours, and the reaction is kept at the temperature for 3 hours to obtain acrylate prepolymer. S2. Add epoxy resin E-51, fluorocarbon modified epoxy resin, and silicone modified acrylate prepolymer to the acrylate prepolymer, stir at 60°C for 2 hours to obtain the pretreated material. S3, adding the core-shell structure corrosion inhibition nano container, functionalized graphene quantum dots, and modified nano zinc oxide into the primary processing material, ultrasonic dispersion for 1 hour at a power of 550 W and a frequency of 20 kHz to obtain a middle processing material, the middle processing material including a solid filler, the solid filler including the core-shell structure corrosion inhibition nano container, the functionalized graphene quantum dots, and the modified nano zinc oxide, detecting a dispersion coefficient of the solid filler, and adjusting the dispersion coefficient of the solid filler until the dispersion coefficient is less than or equal to 15%, the dispersion coefficient being calculated according to the following formula: In the formula, represents the core-shell structure corrosion inhibition nano container, represents the functionalized graphene quantum dots, represents the modified nano zinc oxide, is a functional weight coefficient, wherein = 0.4, = 0.35, = 0.25, is a particle size influence coefficient, wherein = 1.2, = 1.3, = 1.0, is a measured average particle size of a single filler, in nm, is a measured particle size distribution standard deviation of the single filler, in nm; Further, = 0.4, the core-shell structure corrosion inhibition nano container is used to load an inhibitor, the loading amount of the inhibitor is 20-25 wt%, the core-shell structure corrosion inhibition nano container is a core guarantee of long-term corrosion inhibition performance of the coating and has the highest contribution degree to the key performance of the coating, and therefore the weight coefficient is set to 0.4. = 0.35, the functionalized graphene quantum dots are modified by double functional groups, can strengthen the mechanical strength and dense corrosion resistance of the coating, are an important support of core protection performance of the coating, and have a contribution degree only lower than that of the core-shell structure corrosion inhibition nano container, and therefore the weight coefficient is set to 0.35.

[0030] = 0.25, the modified nano zinc oxide is modified by surface organic modification, mainly plays a role in improving the weather resistance of the coating, is an auxiliary performance optimization filler, and has a relatively low contribution degree, and therefore the weight coefficient is set to 0.25.

[0031] = 1.2, the particle size of the core-shell structure corrosion inhibition nano container is 10-30 nm, the core-shell structure corrosion inhibition nano container belongs to a nano filler and has a certain risk of aggregation, and therefore the influence coefficient is set to 1.2.

[0032] = 1.3, the functionalized graphene quantum dots combine the general characteristics of graphene quantum dots, the particle size is usually less than 10 nm, which belongs to a kind of nano-level material, and the specific surface area is larger, the risk of agglomeration is higher than that of the core-shell structure corrosion inhibition nano container, and the requirement for dispersion uniformity is the most stringent, so the influence coefficient is set to 1.3.

[0033] = 1.0, the particle size of the modified nano zinc oxide is 20-50 nm, which is the largest among the three kinds of fillers, the specific surface area is relatively small, the risk of agglomeration is the lowest, and the requirement for dispersion uniformity is relatively loose, so the influence coefficient is set to 1.0; After adjusting the dispersion coefficient to meet the standard, the titanate coupling agent is added to the intermediate treatment object, and the reaction is carried out at 50°C for 1 hour; It should be noted that the dispersion coefficient The laser particle size analyzer (which meets the nano-level particle size detection standard, such as GB / T 19077-2016 "Particle Size Analysis-Laser Diffraction Method") is used for detection, and the detailed measurement steps are as follows: Step 1, respectively, take the core-shell structure corrosion inhibition nano container (particle size 10-30 nm) prepared by sample 1, take 0.1-0.3g, take the functionalized graphene quantum dots (nano-level) prepared by sample 2, take 0.05-0.1g (because the specific surface area of graphene quantum dots is large, the sampling amount needs to be reduced to avoid agglomeration interference), take the modified nano zinc oxide (particle size 20-50 nm) prepared by sample 3, take 0.1-0.3g; Step 2, respectively, add sample 1, sample 2, sample 3 into 3 beakers containing 10-15 mL of absolute ethanol, and use an ultrasonic disperser (power 300-400 W, frequency 20-30 kHz) to ultrasonically treat each beaker for 5-10 minutes to ensure that the fillers are completely dispersed to form a uniform suspension without obvious sedimentation.

[0034] Step 3, start the laser particle size analyzer, use absolute ethanol as a blank control, and calibrate the baseline of the instrument to ensure that the detection background is free of impurities; Sample detection: use a micro-sampler to take the suspension of sample 1, slowly inject it into the detection cell of the laser particle size analyzer, and set the detection parameters (refractive index according to the characteristics of each filler: core-shell structure corrosion inhibition nano container refers to the refractive index of silicon dioxide 1.46, functionalized graphene quantum dots refers to the refractive index of graphene 2.0, modified nano zinc oxide refers to the refractive index of zinc oxide 2.0; Start the detection program, the instrument automatically scans and records the particle size distribution data, and synchronously outputs the average particle size of sample 1 And the standard deviation of the particle size distribution Need to ensure Fall in the interval of 10-30 nm; Sample 2 and Sample 3 are detected in sequence by the same method, and the amounts of functionalized graphene quantum dots of Sample 2 and Sample 3 are obtained respectively , , the amount of modified nano zinc oxide is , , needs to fall in the interval of 20-50nm; Data verification: each sample is detected in parallel for 3 times, and the average value is taken as the final measured data to reduce the detection error.

[0035] Step 4: Substitute the formula to calculate the dispersion coefficient (DC) If the calculated DC≤15%, the dispersion of the mixed solid filler is up to standard; if DC>15%, the ultrasonic dispersion parameters need to be adjusted, the ultrasonic time is prolonged, the ultrasonic power is fine-tuned, or the filler pretreatment process is optimized, such as increasing the coupling agent pre-coating, and re-measuring until DC≤15%.

[0036] S4, cool to 30℃, add hindered amine light stabilizer, dibutyltin dilaurate, light-heat dual responsive curing agent and cage type silsesquioxane maleimide modified amine curing agent, first stir at 800r / min for 30 minutes, then disperse at 2500r / min for 10 minutes; S5, filter to obtain the paint, first irradiate the paint with 365nm UV light (intensity 30mW / cm 2 ) for 30 seconds, and then heat cure at 90℃ for 2 hours to form a coating.

[0037] Example 2 The acrylate-epoxy resin composite coating includes the following raw materials by weight: methyl methacrylate 30 parts, butyl acrylate 20 parts, epoxy resin E-511 15 parts, silicone modified acrylate prepolymer 11.5 parts, fluorocarbon modified epoxy resin 8.5 parts, core-shell structure corrosion inhibitor nano container 6 parts, functionalized graphene quantum dots 2 parts, cage type silsesquioxane maleimide modified amine curing agent 7 parts, hindered amine light stabilizer 2 parts, modified nano zinc oxide 4 parts, titanate coupling agent 1.25 parts, light-heat dual responsive curing agent 3.5 parts, dibutyltin dilaurate 0.3 parts, propylene glycol methyl ether acetate 15 parts, butyl acetate 10 parts.

[0038] The core-shell structure corrosion inhibitor nanocontainer is prepared by the following method: 10 parts of nano-silicon dioxide with a particle size of 10-30 nm are dispersed in a mixture of ethanol / water with a volume ratio of 1:1, 4 parts of benzotriazole are added, and ultrasonic dispersion is performed for 30 minutes; a monomer mixture containing 10 parts of dimethylaminoethyl methacrylate and 1.5 parts of ethylene glycol dimethacrylate is added dropwise, nitrogen is introduced, 0.3 parts of azobisisobutyronitrile is added, and reaction is performed at 65°C for 6 hours; after centrifugal washing and drying, 22.5wt% of the core-shell structure corrosion inhibitor nanocontainer is obtained.

[0039] In addition, the functionalized graphene quantum dots are prepared as follows: graphene oxide quantum dots are dispersed in ammonia water with pH=9, 7 parts of tridecafluorooctyltriethoxysilane and 4 parts of γ-glycidyl ether oxypropyltrimethoxysilane are added, and stirring reaction is performed at 75°C for 18 hours; after dialysis to remove small molecules, freeze-drying is performed, and functionalized graphene quantum dots grafted with double functional groups are obtained.

[0040] The cage silsesquioxane maleimide modified amine curing agent is prepared by the following method: 45 parts of isobutyltrichlorosilane is dissolved in 90 parts of toluene, under ice water bath cooling, 30 parts of deionized water is slowly added dropwise, 17.5 parts of triethylamine is added at the same time, after the dropwise addition is completed, the temperature is increased to 95°C for reflux reaction for 10 hours; after the reaction is completed, the generated salt is removed by filtration, and the solvent is removed by distillation under reduced pressure, and 35 parts of isobutyl cage silsesquioxane is obtained; The above-mentioned 35 parts of isobutyl cage silsesquioxane is dissolved in 70 parts of toluene, 10 parts of 3-aminopropyltriethoxysilane and 0.75 parts of tin octoate are added, the temperature is increased to 110°C for reaction under nitrogen protection for 13 hours, after the reaction is completed, the unreacted monomer and solvent are removed by distillation under reduced pressure, and 25 parts of aminopropyl isobutyl cage silsesquioxane is obtained; The 25 parts of aminopropyl isobutyl cage silsesquioxane is dissolved in toluene, 12 parts of N-(2-aminoethyl) maleimide is added, and reaction is performed at 70°C for 5 hours, and the solvent is removed by distillation under reduced pressure, and the cage silsesquioxane maleimide modified amine curing agent is obtained.

[0041] The light-heat dual-responsive curing agent is furanmethylamine-2-hydroxy-2-methylpropiophenone adduct, and the structural formula is: (CH3)2C(OH)C(=NCH2C4H3O)C(O)CH3.

[0042] The modified nano-zinc oxide is prepared by the following method: 10 parts of nano-zinc oxide powder with a particle size of 20-50 nm is dispersed in anhydrous ethanol, and ultrasonic treatment is performed for 30 minutes to form a suspension; after heating to 60±2°C, stearic acid-ethanol solution is added dropwise, the amount of stearic acid is 20% of the mass of nano-zinc oxide, and stirring reaction is performed under nitrogen protection for 4 hours; after the reaction is completed, centrifugal separation is performed, washing with anhydrous ethanol is performed for 3 times, and vacuum drying is performed at 80°C for 12 hours, and the surface-organic modified nano-zinc oxide is obtained.

[0043] It should be noted that the photo-thermal dual-responsive curing agent is prepared by the following method: Step one, according to the weight part, 2-furfuryl formaldehyde 15 parts and anhydrous ethanol 30 parts are mixed, and the temperature is reduced to 2.5℃ in ice bath; slowly add concentrated ammonia water 10 parts, keep the temperature <10℃, after dropping, warm up to 25℃ for 2 hours; add sodium borohydride 5 parts, reduce at 40℃ for 3 hours, remove the solvent by reduced pressure distillation, get furfuryl amine crude product; Step two, according to the weight part, furfuryl amine 10 parts, 2-hydroxy-2-methyl propiophenone 12 parts are added into toluene 50 parts, and p-toluenesulfonic acid 0.5 parts is added; heated to 110±2℃ reflux reaction for 6 hours; the reaction liquid is cooled and washed with water until neutral, dried with anhydrous magnesium sulfate, and the toluene is removed by reduced pressure distillation, to get yellow viscous liquid, which is the photo-thermal dual-responsive curing agent.

[0044] The preparation method of the acrylate-epoxy resin composite coating includes the following steps: S1, methyl methacrylate, butyl acrylate, propylene glycol methyl ether acetate and butyl acetate are added into the reaction kettle, heated to 85℃, and 10 parts of butyl acetate solution containing 3 parts of azobisisobutyronitrile is added dropwise, dropwise for 2.5 hours, and then kept for 3.5 hours to obtain acrylate prepolymer; S2, add epoxy resin E-51, fluorocarbon modified epoxy resin, and organic silicon modified acrylate prepolymer to the acrylate prepolymer, and stir at 65℃ for 2.5 hours to obtain the primary processing material; S3, add core-shell structure corrosion inhibition nano container, functionalized graphene quantum dots and modified nano zinc oxide to the primary processing material, and ultrasonic dispersion for 1.5 hours under the power of 600W and the frequency of 25kHz to obtain the intermediate processing material, which includes solid fillers, and the solid fillers include core-shell structure corrosion inhibition nano container, functionalized graphene quantum dots and modified nano zinc oxide; the dispersion coefficient of the solid fillers is detected, and the dispersion coefficient of the solid fillers is adjusted until ≤15%, and the dispersion coefficient is calculated according to the following formula: In the formula, represents the core-shell structure corrosion inhibition nano container, represents the functionalized graphene quantum dots, represents the modified nano zinc oxide, is the functional weight coefficient, wherein =0.4、 =0.35、 =0.25, is the particle size influence coefficient, wherein =1.2、 =1.3, = 1.0, the measured average particle size of the single filler, the standard deviation of the measured particle size distribution of the single filler; After adjusting the dispersion coefficient to meet the standard, add a titanate coupling agent to the intermediate treatment, and react at 55°C for 1.5 hours; S4, cool to 35°C, add a hindered amine light stabilizer, dibutyltin dilaurate, a light-thermal dual-responsive curing agent, and a cage-type silsesquioxane maleimide modified amine curing agent, first stir at 800 r / min for 40 minutes, then high-speed disperse at 2500 r / min for 20 minutes; S5, after filtering, the paint is obtained, which is first irradiated with 365 nm UV light (intensity 30 mW / cm 2 ) for 30 seconds, and then heat cured at 90°C for 2 hours to form a coating.

[0045] Example 3 The acrylate-epoxy resin composite coating includes the following raw materials by weight: 35 parts of methyl methacrylate, 25 parts of butyl acrylate, 20 parts of epoxy resin E-5120, 15 parts of silicone-modified acrylate prepolymer, 12 parts of fluorocarbon-modified epoxy resin, 8 parts of core-shell structure corrosion inhibitor nano container, 3 parts of functionalized graphene quantum dots, 10 parts of cage-type silsesquioxane maleimide modified amine curing agent, 3 parts of hindered amine light stabilizer, 6 parts of modified nano zinc oxide, 2 parts of titanate coupling agent, 5 parts of light-thermal dual-responsive curing agent, 0.5 parts of dibutyltin dilaurate, 20 parts of propylene glycol methyl ether acetate, and 15 parts of butyl acetate.

[0046] The core-shell structure corrosion inhibitor nano container is prepared by the following method: 12 parts of nano silicon dioxide with a particle size of 30 nm are dispersed in a mixture of ethanol / water with a volume ratio of 1:1, 5 parts of benzotriazole are added, and ultrasonic dispersion is performed for 35 minutes; a monomer mixture containing 12 parts of dimethylaminoethyl methacrylate and 2 parts of ethylene glycol dimethyl acrylate is added dropwise, nitrogen is introduced, and 0.4 parts of azobisisobutyronitrile is added, and the reaction is carried out at 70°C for 7 hours; after centrifugal washing and drying, the core-shell structure corrosion inhibitor nano container with a corrosion inhibitor loading of 25wt% is obtained.

[0047] In addition, the functionalized graphene quantum dots are prepared as follows: graphene oxide quantum dots are dispersed in ammonia water with pH=9, 8 parts of tridecafluorooctyltriethoxysilane and 5 parts of γ-glycidoxypropyltrimethoxysilane are added, and the reaction is carried out at 80°C for 20 hours under stirring; after dialysis to remove small molecules, freeze-drying is performed to obtain functionalized graphene quantum dots grafted with double functional groups.

[0048] The cage silsesquioxane maleimide modified amine curing agent is prepared by the following method: 50 parts of isobutyltrichlorosilane is dissolved in 100 parts of toluene, under ice water bath cooling, 35 parts of deionized water is slowly added dropwise, while 20 parts of triethylamine is added, after the dropwise addition is completed, the temperature is raised to 110°C and refluxed for 12 hours; after the reaction is completed, the generated salt is removed by filtration, the solvent is removed by distillation under reduced pressure, and 40 parts of isobutyl cage silsesquioxane is obtained; The above 40 parts of isobutyl cage silsesquioxane is dissolved in 80 parts of toluene, 12 parts of 3-aminopropyltriethoxysilane and 1 part of stannous octoate are added, and the temperature is raised to 120°C under nitrogen protection for 16 hours; after the reaction is completed, the unreacted monomer and solvent are removed by distillation under reduced pressure, and 27 parts of aminopropyl isobutyl cage silsesquioxane is obtained; The aminopropyl isobutyl cage silsesquioxane 27 parts is dissolved in toluene, 14 parts of N-(2-aminoethyl) maleimide is added, and the reaction is carried out at 75°C for 6 hours; the solvent is removed under reduced pressure to obtain a cage silsesquioxane maleimide modified amine curing agent.

[0049] The photo-thermal dual-responsive curing agent is furfurylamine-2-hydroxy-2-methylpropiophenone adduct, and its structural formula is: (CH3)2C(OH)C(=NCH2C4H3O)C(O)CH3.

[0050] The modified nano zinc oxide is prepared by the following method: 12 parts of nano zinc oxide powder with a particle size of 20-50 nm is dispersed in anhydrous ethanol, and ultrasonic treatment is carried out for 35 minutes to form a suspension; after heating to 60°C, stearic acid-ethanol solution is added dropwise, the amount of stearic acid is 25% of the mass of nano zinc oxide, and the reaction is carried out under nitrogen protection for 5 hours; after the reaction is completed, centrifugal separation is carried out, and the product is washed with anhydrous ethanol for 4 times, and vacuum dried at 85°C for 14 hours to obtain nano zinc oxide with surface organic modification.

[0051] It should be noted that the photo-thermal dual-responsive curing agent is prepared by the following method: Step one, according to weight parts, 17 parts of 2-furfuryl aldehyde is mixed with 32 parts of anhydrous ethanol, and the temperature is reduced to 5°C by ice bath cooling; 12 parts of concentrated ammonia water is slowly added dropwise, the temperature is kept <10°C, after the dropwise addition is completed, the temperature is raised to 27°C and the reaction is carried out for 3 hours; 6 parts of sodium borohydride is added, and the reduction reaction is carried out at 45°C for 4 hours; the solvent is removed by distillation under reduced pressure to obtain crude furfurylamine; Step two, according to weight parts, 12 parts of furfurylamine obtained in step one and 14 parts of 2-hydroxy-2-methylpropiophenone are added to 55 parts of toluene, and 0.7 parts of p-toluenesulfonic acid is added; the temperature is raised to 110±2°C and refluxed for 7 hours; after the reaction liquid is cooled, it is washed with water until it is neutral, dried with anhydrous magnesium sulfate, and toluene is removed by distillation under reduced pressure to obtain a yellow viscous liquid, which is the photo-thermal dual-responsive curing agent.

[0052] As Figure 1The application relates to a preparation method of an acrylate-epoxy resin composite coating, which comprises the following steps: S1, methyl methacrylate, butyl acrylate, propylene glycol methyl ether acetate and butyl acetate are added into a reaction kettle, the temperature is raised to 90 DEG C, 12 parts of a butyl acetate solution containing 2-4 parts of azobisisobutyronitrile are added dropwise, dropwise addition is completed within 3 hours, and the reaction is preserved for 4 hours, so that an acrylate prepolymer is obtained; S2, epoxy resin E-51, fluorocarbon modified epoxy resin and organic silicon modified acrylate prepolymer are added into the acrylate prepolymer, stirring is carried out at 70 DEG C for 3 hours, and a primary processing product is obtained; S3, core-shell structure corrosion-inhibiting nano containers, functionalized graphene quantum dots and modified nano zinc oxide are added into the primary processing product, ultrasonic dispersion is carried out at a power of 650 W and a frequency of 30 kHz for 2 hours, a middle processing product is obtained, the middle processing product comprises solid fillers, the solid fillers comprise the core-shell structure corrosion-inhibiting nano containers, the functionalized graphene quantum dots and the modified nano zinc oxide, a dispersion coefficient of the solid fillers is detected, and the dispersion coefficient of the solid fillers is adjusted until the dispersion coefficient is less than or equal to 15%, the dispersion coefficient is calculated according to the following formula: In the formula, represents the core-shell structure corrosion-inhibiting nano containers, represents the functionalized graphene quantum dots, represents the modified nano zinc oxide, is a functional weight coefficient, wherein = 0.4, = 0.35, = 0.25, is a particle size influence coefficient, wherein = 1.2, = 1.3, = 1.0, is a measured average particle size of a single filler, is a measured particle size distribution standard deviation of the single filler; After the dispersion coefficient meets the standard, a titanate coupling agent is added into the middle processing product, and reaction is carried out at 60 DEG C for 2 hours; S4, the temperature is lowered to 40 DEG C, a hindered amine light stabilizer, dibutyltin dilaurate, a light-heat dual-responsive curing agent and a cage-type silsesquioxane maleimide modified amine curing agent are added, stirring is carried out at 800 r / min for 50 minutes, and high-speed dispersion is carried out at 2500 r / min for 30 minutes; S5, the coating is obtained after filtration, the coating is irradiated with 365 nm UV light (intensity 30 mW / cm²) for 30 seconds, and heat curing is carried out at 90 DEG C for 2 hours, so that a coating layer is formed.

[0053] Comparative Example 1, the difference between this comparative example and Example 2 is only that the core-shell structure corrosion-inhibiting nanocontainer 6 parts is deleted and an equal amount of ordinary nano-SiO2 is added, and the SiO2 is not pH-responsive coated.

[0054] Comparative Example 2, the difference between this comparative example and Example 2 is only that the functionalized graphene quantum dot 2 parts is deleted and no substitute is added.

[0055] Comparative Example 3, the difference between this comparative example and Example 2 is only that the light-heat dual-responsive curing agent 3.5 parts is replaced with an equal amount of ordinary amine curing agent diethylenetriamine 2.1 parts.

[0056] Comparative Example 4, the difference between this comparative example and Example 2 is only that the modified nano-zinc oxide 4 parts is deleted and no substitute is added.

[0057] Comparative Example 5, the difference between this comparative example and Example 2 is only that the core-shell structure corrosion-inhibiting nanocontainer 6 parts and the functionalized graphene quantum dot 2 parts are deleted, and an equal amount of ordinary nano-SiO2 4 parts and carbon black 2 parts are added.

[0058] Experiments were performed on the coatings of Examples 1-3 and Comparative Examples 1-5, and the experiments were as follows: Salt spray resistance: ASTM B117 Self-repairing efficiency: After 2h repair at 80°C, the recovery rate of the low-frequency impedance modulus value (|Z|0. 01 Hz) was calculated Fluorescent diagnosis: 365nm ultraviolet lamp irradiation, observe the fluorescence intensity at the damage site (0-5 levels, 5 levels are the strongest) Antibacterial rate: ISO22196 (Escherichia coli / Staphylococcus aureus).

[0059] The experimental results are as follows: From the above table, when the coating is damaged and the local pH is increased, the core-shell container targets the release of benzotriazole corrosion inhibitor, Example 2: salt spray resistance 6200h; the functionalized graphene quantum dot forms a continuous conductive network, uniformly disperses the electrochemical corrosion current, and inhibits the expansion of pitting corrosion, and the salt spray resistance of Comparative Example 2 is reduced to 4800h; when both are present, the salt spray resistance time is only 94% higher than that of Comparative Example 1 using ordinary SiO2, proving the multiplication effect of electrochemical shielding and intelligent corrosion inhibition.

[0060] In this embodiment, the dynamic DA bond in the light-thermal curing agent reversibly reorganizes at 80°C, achieving microcrack self-repair, with a repair rate of 88% in Example 2; the epoxy groups on the surface of graphene quantum dots participate in crosslinking, strengthening the filler-resin interface bonding, and the adhesion remains at level 0; after replacing the ordinary curing agent in Comparative Example 3, the repair rate is ≤10% and the adhesion decreases to level 2 due to the absence of dynamic bonds, proving the irreplaceability of the dynamic network and the interface chemical bonding.

[0061] In this embodiment, nano zinc oxide and graphene quantum dots form an ultraviolet absorption gradient, improving weather resistance; the two synergistically destroy microbial membrane structures, with an antibacterial rate of 96% in Example 2; after deleting nano zinc oxide in Comparative Example 4, the antibacterial rate decreases to 70%, revealing that graphene quantum dots can amplify the bacteriostatic efficiency of nano zinc oxide.

[0062] It is worth noting that functionalized graphene quantum dots emit 450 nm blue light under 365 nm ultraviolet light, precisely locating micron-level damage with a fluorescence level of 5, which is unprecedented in the paint field: after deleting in Comparative Example 2, the fluorescence completely disappears, proving that it cannot be replaced by other conductive fillers (such as carbon black in Comparative Example 5); this feature greatly improves maintenance efficiency, reducing the naked eye recognition time from >48 h to instant. In addition, the long-term effectiveness of self-repair in extreme environments is good, and the dynamic DA bond network remains active in wet heat / salt spray cycles, with the impedance recovery rate of the coating in Example 2 still >85% after 5 cycles of damage-repair cycles - breaking through the life bottleneck of existing self-repair coatings ≤3 cycles, and Comparative Example 3 fails after the first repair. The core-shell container releases corrosion inhibitors in response to local pH changes, combined with the charge distribution regulation of graphene quantum dots, achieving enrichment of corrosion inhibitors at rust spots, with SEM-EDS showing an 8-fold increase in BTA concentration in the Fe element region, solving the problem of 90% waste of effective components caused by non-controlled release of traditional corrosion inhibitors.

[0063] The core-shell structure corrosion-inhibiting nano-container releases benzotriazole corrosion inhibitor in a targeted manner when the coating is damaged, causing local changes in pH value, thereby blocking the corrosion process; the functionalized graphene quantum dots form a continuous conductive network to disperse the electrochemical corrosion current and inhibit the spread of pitting corrosion. The combination of the two significantly improves the salt spray resistance of the coating. For example, the salt spray resistance of Example 2 is up to 6200 h, which is 94% higher than that of Comparative Example 1 using only ordinary nano-SiO2 and 30% higher than that of Comparative Example 2 without functionalized graphene quantum dots. The dynamic covalent bond of the photo-thermal dual-responsive curing agent reversibly reorganizes under thermal triggering, achieving self-repair of microcracks. The self-repair efficiency of Example 2 is 88%. The cage-type silsesquioxane maleimide-modified amine curing agent introduces a rigid skeleton to ensure the hardness of the coating, and the pencil hardness of Example 2 is 4H. The combination of the two takes into account both repair capability and structural strength, and the self-repair efficiency is 78% higher than that of Comparative Example 3 using ordinary amine curing agents, and the adhesion is improved from level 2 to level 0. The modified nano-zinc oxide absorbs ultraviolet light and damages the cell membrane of microorganisms, and the functionalized graphene quantum dots form an ultraviolet absorption gradient with it, amplifying the antibacterial effect. The antibacterial rate of Example 2 is 96%, which is 26% higher than that of Comparative Example 4 without modified nano-zinc oxide; at the same time, the combination of the two improves the weather resistance of the coating and reduces the performance degradation caused by light aging.

[0064] The functionalized graphene quantum dots can locate micron-level damage by changes in fluorescence intensity under ultraviolet light, and the fluorescence diagnosis level of Example 2 is level 5. The photo-thermal dual-responsive curing agent completes repair after damage localization through thermal triggering, and at the same time, the core-shell structure corrosion-inhibiting nano-container releases corrosion inhibitor to prevent secondary corrosion. Compared with Comparative Example 2 without functionalized graphene quantum dots, Example 2 realizes immediate identification of damage, and compared with Comparative Example 3 using ordinary curing agents, Example 2 realizes multiple cycle repair.

[0065] In summary, the core-shell container of the present application can target release of corrosion inhibitor when the coating is damaged and the local pH value changes, and the functionalized graphene quantum dots can form a conductive network to inhibit the expansion of pitting corrosion, both of which can greatly improve the salt spray resistance. The salt spray resistance of Example 2 is 6200h, which is 94% higher than that of Comparative Example 1. The dynamic bond in the light-thermal curing agent can reversibly reorganize at 80℃, realizing efficient self-repair of micro-cracks. The repair rate of Example 2 is 88%, and the effect is still good after multiple cycles, breaking through the bottleneck of the number of repair times of traditional coatings. The fluorescence characteristics of functionalized graphene quantum dots under ultraviolet light can accurately locate micron-level damage, shorten the maintenance identification time from more than 48 hours to instant, and greatly improve the maintenance efficiency. At the same time, the synergistic effect of nanometer zinc oxide and graphene quantum dots can enhance the ultraviolet shielding and antibacterial properties. The antibacterial rate of Example 2 is 96%. In addition, through the scientific proportioning and synergistic effect of various components, the paradox that the hardness and toughness, corrosion resistance and workability of traditional coatings are difficult to balance is broken. For example, Example 3 realizes a good balance between 5H pencil hardness and 90% self-repair rate, and the adhesion reaches 0 level, with excellent comprehensive performance. It provides long-term protection in all time domains and multiple dimensions for equipment in extreme environments, and greatly improves the economic efficiency of marine equipment throughout the cycle.

[0066] It is worth noting that in the uniformly doped coating, the functionalized graphene quantum dots can be specifically excited by ultraviolet light at the damage site and realize fluorescence tracing. The core lies in the synergistic effect of the microenvironment change of the damage area and the optical response mechanism of the quantum dots. The functionalized graphene quantum dots are grafted and modified by the double functional groups of tridecafluorooctyltriethoxysilane and γ-glycidoxypropyltrimethoxysilane. Graphene quantum dots themselves have excellent fluorescence emission capability and can emit specific wavelength fluorescence under ultraviolet light (such as 365nm), such as the 450nm blue light mentioned in the examples. The epoxy groups from γ-glycidoxypropyltrimethoxysilane on the surface of the grafted graphene quantum dots can form chemical bonds with the resin matrix, and the fluorocarbon chain from tridecafluorooctyltriethoxysilane enhances its uniformity in the coating.

[0067] When the coating has micron-level defects (such as cracks, scratches), the following changes occur in the damaged area, which in turn affects the fluorescence properties of the functionalized graphene quantum dots. The damage causes the chemical bonding between the quantum dots and the resin matrix to break, and the quantum dots change from a bound state to a free state. The surface energy state changes, the fluorescence quantum yield increases, and when not bound by the matrix, non-radiative transitions decrease, and the fluorescence intensity increases. Seawater, oxygen corrosion medium enters the coating through the defects and interacts with the functional groups (such as epoxy groups and fluorocarbon chains) on the surface of the quantum dots, such as hydrogen bonds and polar adsorption, changing the local electronic environment and further enhancing fluorescence emission. The air-coating interface at the damage site changes the propagation path of ultraviolet light, allowing more photons to be absorbed by the quantum dots in this area, resulting in stronger fluorescence. Although the quantum dots are uniformly distributed in the coating, there is a significant difference in fluorescence intensity between the damaged area and the intact area. The quantum dots are tightly bound to the resin, and the fluorescence is slightly quenched by the matrix, resulting in stable background fluorescence. Through the above mechanisms, the fluorescence is significantly enhanced due to changes in the microenvironment, forming a bright damage point and a dark surrounding contrast, which can be clearly identified under ultraviolet light, such as the fluorescence diagnosis level of 5 in Example 2.

[0068] The above specific embodiments are only several optional embodiments of the present application, and based on the technical solutions of the present application and the related inspirations of the above embodiments, those skilled in the art can make various alternative improvements and combinations on the above specific embodiments.

Claims

1. An acrylic-epoxy resin composite coating, characterized in that, Including the following parts by weight of raw materials: Methyl methacrylate 25-35 parts, butyl acrylate 15-25 parts, epoxy resin E-511 0-20 parts, silicone-modified acrylate prepolymer 8-15 parts, fluorocarbon-modified epoxy resin 5-12 parts, core-shell structure corrosion-inhibiting nanocontainer 4-8 parts, functionalized graphene quantum dots 1-3 parts, cage-type silsesquioxane maleimide-modified amine curing agent 4-10 parts, hindered amine light stabilizer 1-3 parts, modified nano zinc oxide 2-6 parts, titanate coupling agent 0.5-2 parts, photo-thermal dual-responsive curing agent 2-5 parts, dibutyltin dilaurate 0.1-0.5 parts, propylene glycol methyl ether acetate 10-20 parts, butyl acetate 5-15 parts.

2. The acrylate-epoxy resin composite coating according to claim 1, characterized in that, The core-shell structured corrosion-inhibiting nanocontainer was prepared by the following method: 8-12 parts of nano-silica with a particle size of 10-30 nm were dispersed in a 1:1 volume ratio of ethanol / water, and 3-5 parts of benzotriazole were added. The mixture was ultrasonically dispersed for 25-35 minutes. A monomer mixture containing 8-12 parts of dimethylaminoethyl methacrylate and 1-2 parts of ethylene glycol dimethacrylate was added dropwise. After purging with nitrogen, 0.2-0.4 parts of azobisisobutyronitrile were added, and the mixture was reacted at 60-70℃ for 5-7 hours. After centrifugation, washing, and drying, a core-shell structured corrosion-inhibiting nanocontainer with a corrosion inhibitor loading of 20-25 wt% was obtained.

3. The acrylic-epoxy resin composite coating according to claim 1, characterized in that, The functionalized graphene quantum dots are prepared as follows: Graphene oxide quantum dots were dispersed in ammonia water at pH 9, and 6-8 parts of tridecafluorooctyltriethoxysilane and 3-5 parts of γ-glycidyl etheroxypropyltrimethoxysilane were added. The mixture was stirred at 70-80℃ for 16-20 hours. After dialysis to remove small molecules, the mixture was freeze-dried to obtain bifunctionalized grafted graphene quantum dots.

4. The acrylate-epoxy resin composite coating according to claim 1, characterized in that, The cage-type silsesquioxane maleimide-modified amine curing agent is prepared by the following method: Dissolve 40-50 parts of isobutyltrichlorosilane in 80-100 parts of toluene. Under ice-water bath cooling, slowly add 25-35 parts of deionized water and 15-20 parts of triethylamine dropwise. After the addition is complete, heat to 80-110℃ and reflux for 8-12 hours. After the reaction is complete, filter to remove the generated salt, and remove the solvent by vacuum distillation to obtain 30-40 parts of isobutyl cage-like silsesquioxane. Dissolve 30-40 parts of the above isobutyl cage-like silsesquioxane in 60-80 parts of toluene, add 8-12 parts of 3-aminopropyltriethoxysilane and 0.5-1 parts of tin octoate, and heat to 100-120℃ under nitrogen protection for 10-16 hours. After the reaction is completed, remove unreacted monomers and solvents by vacuum distillation to obtain 23-27 parts of aminopropyl isobutyl cage-like silsesquioxane. Dissolve 23-27 parts of aminopropyl isobutyl cage-type silsesquioxane in toluene, add 10-14 parts of N-(2-aminoethyl)maleimide, react at 65-75℃ for 4-6 hours, remove the solvent under reduced pressure to obtain cage-type silsesquioxane maleimide modified amine curing agent.

5. The acrylic-epoxy resin composite coating according to claim 1, characterized in that, The photo-thermal dual-responsive curing agent is furanylamine-2-hydroxy-2-methylphenylacetone adduct, with the structural formula: (CH3)2C(OH)C(=NCH2C4H3O)C(O)CH3.

6. The acrylic-epoxy resin composite coating according to claim 1, characterized in that, The modified nano zinc oxide was prepared by the following method: Disperse 8-12 parts of nano zinc oxide powder with a particle size of 20-50nm in anhydrous ethanol and sonicate for 25-35 minutes to form a suspension. After heating to 60±2℃, add stearic acid-ethanol solution dropwise. The amount of stearic acid is 15-25% of the mass of nano zinc oxide. Stir the reaction under nitrogen protection for 3-5 hours. After the reaction was completed, the mixture was centrifuged, washed 2-4 times with anhydrous ethanol, and vacuum dried at 75-85℃ for 10-14 hours to obtain surface-organically modified nano-zinc oxide.

7. The acrylate-epoxy resin composite coating according to claim 1, characterized in that, The photo-thermal dual-responsive curing agent is prepared by the following method: By weight, 13-17 parts of 2-furan carbaldehyde were mixed with 28-32 parts of anhydrous ethanol, cooled to 0-5°C in an ice bath, and 8-12 parts of concentrated ammonia were slowly added dropwise while maintaining the temperature <10°C. After the addition was complete, the temperature was raised to 23-27°C and reacted for 1-3 hours. Then, 4-6 parts of sodium borohydride were added and the reduction reaction was carried out at 35-45°C for 2-4 hours. The solvent was removed by vacuum distillation to obtain crude furanylmethylamine. By weight, 8-12 parts of furanylmethylamine and 10-14 parts of 2-hydroxy-2-methylphenylacetone obtained in step one are added to 45-55 parts of toluene, and 0.3-0.7 parts of p-toluenesulfonic acid are added. The mixture is heated to 110±2℃ and refluxed for 5-7 hours. After the reaction solution is cooled, it is washed with water until neutral, dried with anhydrous magnesium sulfate, and toluene is removed by vacuum distillation to obtain a yellow viscous liquid, which is the photo-thermal dual-responsive curing agent.

8. A method for preparing an acrylic-epoxy resin composite coating as described in any one of claims 1-7, characterized in that, Includes the following steps: S1. Add methyl methacrylate, butyl acrylate, propylene glycol methyl ether acetate and butyl acetate to a reaction vessel, heat to 80℃-90℃, and dropwise add 8-12 parts of butyl acetate solution containing 2-4 parts of azobisisobutyronitrile over 2-3 hours. Keep the reaction at the temperature for 3-4 hours to obtain acrylate prepolymer. S2. Add epoxy resin E-51, fluorocarbon modified epoxy resin, and silicone modified acrylate prepolymer to the acrylate prepolymer, stir at 60-70℃ for 2-3 hours to obtain the pretreated product. S3. Add core-shell structured corrosion-inhibiting nanocontainers, functionalized graphene quantum dots, and modified nano-zinc oxide to the primary treated material. Disperse the mixture ultrasonically for 1-2 hours at a power of 550-650W and a frequency of 20-30kHz to obtain the intermediate treated material. The intermediate treated material contains solid fillers, including core-shell structured corrosion-inhibiting nanocontainers, functionalized graphene quantum dots, and modified nano-zinc oxide. Detect the dispersion coefficient of the solid fillers until it is adjusted. ≤15%, the dispersion factor is calculated according to the following formula: In the formula, Represents a core-shell structured corrosion-inhibiting nanocontainer. Representative functionalized graphene quantum dots, Represents modified nano zinc oxide, Here are the functional weight coefficients, where =0.4、 =0.35、 =0.25, is the particle size influence coefficient, where =1.2、 =1.3、 =1.0, The measured average particle size of a single filler is given. The standard deviation of the measured particle size distribution for a single filler is given. After adjusting the dispersion coefficient to meet the standard, add titanate coupling agent to the intermediate-grade material and react at 50-60℃ for 1-2 hours; S4. Cool to 30-40℃, add hindered amine light stabilizer, dibutyltin dilaurate, photo-thermal dual-responsive curing agent and cage-type silsesquioxane maleimide modified amine curing agent, stir for 30-50 minutes, and then disperse at high speed for 10-30 minutes. S5. The coating is obtained after filtration.

9. The method for preparing an acrylate-epoxy resin composite coating according to claim 8, characterized in that, In S3, the ultrasonic power is 550-650W and the frequency is 20-30kHz.

10. The method for preparing an acrylate-epoxy resin composite coating according to claim 8, characterized in that, In step S4, the mixture is first stirred at 800 r / min for 30-50 minutes, and then dispersed at 2500 r / min for 10-30 minutes.

Citation Information

Cited By

  • Preparation method of high-corrosion-resistance color coated steel plate

    CN121610159A

  • Epoxy adhesive material for marine environment steel bridge deck pavement and application thereof

    CN122503057A